Financial resource contribution to production growth and return on producer’s capital - Villalobos Céspedes, Daniel (2018)
Financial resource contribution to production growth is a taboo issue in economic theory, especially if its source is the financial capital, which is part of the dynamic of any vigorous economy. Financial capital is a pivotal instrument of production growth due to the fact that its participation contributes to the process of transforming and transferring values from inputs to outputs. By doing so, financial capital encourages producers to generate not only outputs but also profit. Producers must transmute financial capital into financial resources in order to obtain output and profit. Therefore, the rate of interest becomes the way in which financial capital and producers get into the production process. This is to what this theoretical research is concerning.